Models and Implementation of Curriculum Development in Schools - Fatoni, Mahfud Heru; Santoso, Baron; Syarifuddin, Hamid; Hanani, Hanif (Journal of International Multidisciplinary Research, 2024)
Curriculum development cannot be separated from various aspects that influence it. Various curriculum models have been developed by curriculum, education and psychology experts. The curriculum development model is an alternative procedure for designing, implementing and evaluating a curriculum. Therefore, the curriculum development model must be able to describe a learning planning system process that can meet various needs and standards of educational success. This research aims to examine curriculum development models and their implementation in schools. In this article the author uses library research or what could be called qualitative research which obtains data from appropriate journals, articles and books. In the search, researchers will collect as much information as possible from related libraries. These library sources can be obtained from: books, journals, magazines, research results such as theses and dissertations, and other appropriate sources. If researchers have obtained relevant literature, it will be compiled regularly for use in research. The research results found that in developing the curriculum, teachers can choose several models including the Tyler Model, Administrative Model, Grassroots Approach Model, Demonstration Model, Beauchamp System Model or Beauchamp Model, Roger Model, Problem Solving Model and Taba Reverse Model. Curriculum development procedures include curriculum planning, curriculum organization, staff placement, and curriculum control. Meanwhile, curriculum implementation is the process of applying ideas, concepts, policies, in the form of practical actions, so that it creates impacts, both in the form of changes in students' knowledge, skills, as well as values and attitudes. The success of curriculum implementation is also determined by communication about the implementation plan and support from all resources in implementation.